2000
DOI: 10.1177/002215540004800904
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression of Receptors for IL-6, LIF, and CNTF in Regenerating Skeletal Muscles

Abstract: The biological actions of interleukin-6 (IL-6), leukemia inhibitory factor (LIF), and ciliary neurotrophic factor (CNTF) are mediated via respective functional receptor complexes consisting of a common signal-transducing component, gp130, and other specific receptor components, IL-6 receptor α (IL-6R), LIF receptor β (LIFR), and CNTF receptor α (CNTFR). IL-6, LIF, and CNTF are implicated in skeletal muscle regeneration. However, the cell populations that express these receptor components in regenerating muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 36 publications
3
51
0
Order By: Relevance
“…These results suggest that IL-6 may not play a role in mediating insulin resistance in skeletal muscle. This agrees with reports indicating exceedingly low levels of IL-6 receptors expressed in muscle cells (36,37). Alternatively, the concentrations of IL-6 used in our current study may be too low to elicit a response in skeletal muscle.…”
Section: Discussionsupporting
confidence: 92%
“…These results suggest that IL-6 may not play a role in mediating insulin resistance in skeletal muscle. This agrees with reports indicating exceedingly low levels of IL-6 receptors expressed in muscle cells (36,37). Alternatively, the concentrations of IL-6 used in our current study may be too low to elicit a response in skeletal muscle.…”
Section: Discussionsupporting
confidence: 92%
“…Two major intracellular signal transduction pathways, namely the Janus kinase (JAK)/signal transducer and activator of transcription (STAT) and the extracellular signal-regulated kinase (ERK) pathways, are known to mediate most of the biological effects of the IL-6-type cytokines [28]. During the injury-induced muscle regeneration, it has been shown that the mRNAs for IL-6, LIF, gp130, and LIFR are quickly induced on injury [29][30][31]. However, the role of OSM in myoblast differentiation and muscle regeneration remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Among the cytokines secreted by proinflammatory macrophages, significantly increased expression of IL-6 and IL-6R mRNA was first seen in the injury site at 3 h after cardiotoxin injury (11,12). Exogenous recombination IL-6 influence the proliferation and differentiation of cultured myoblast derived from human or mouse muscle.…”
mentioning
confidence: 99%